Pesantren dan Islam Puritan: Pelembagaan Tajdid Keagamaan di Lembaga Pendidikan Islam - M. Arfan Mu’ammar (Universitas Darussalam Gontor, 2015)
In the 18th century, the leaders of Muslim reformers focused their movement to break the internal rigidity in the form of tauhîd purification against the dominance of schools and heretical eradication which commonly called the religious purification (tajdîd al-fikr al-Islâmî). Therefore, at the end of the 19th century popping figures reformer (mujadid) which called on Muslims to take modern civilization that support progress in the sense of rationalization and technical. At that time also, a wave of renewal of thought emerged in Indonesia as echoed by Ahmad Dahlan, Sheikh Ahmad Soorkati, KH. Zamzam, etc. Movement purification of Islam in Indonesia is implemented with the establishment of educational institutions such as pesantren and formal schools, as the form and attempt to inherit and maintain ideological purists like Pondok Modern Muhammadiyah Paciran, Lamongan; Pesantren al-Ishlah Sendangagung, Paciran Lamongan; Pesantren al-Islam Tenggulun, Lamongan Solokuro; Pesantren Maskumambang, Dukun Gresik; and Pesantren Persis in Pasuruan Bangil. These five pesantrens have been selected as the research because that had been considered to represent the ideological purists in Indonesia and some organizations and institutions that embrace the puritan ideology. This paper will discuss the topic of pesantren and Puritan Islamic from the standpoint of its history and dynamics, relation with tajdîd, and renewal of existing typologies in boarding schools, as well as how tajdîd be implemented in boarding institutions.